Implementation of Teacher’s Performance Academic Supervision - Erifal, Erifal (PPSDP International Journal of Education, 2023)
The purpose of this study is to ascertain the impact of academic supervision on teachers’ performance at SMA Negeri 1 Kayuagung. using observation, documentation, interviews, and literature reviews as data collecting methods. The data analysis method employs methods for descriptive and qualitative analysis. According to the study’s findings, academic supervision was implemented after various steps of planning, carrying it out, receiving input, and monitoring its outcomes. The supervision instrument used to conduct the evaluation was taken directly from the new paradigm curriculum supervision instrument. The readiness of the administration of learning tools, the implementation of learning, and the evaluation of teacher learning are all impacted by the school principal’s assessment based on academic supervision tools. The performance of teachers at SMA Negeri 1 Kayuagung has improved as a result of positive comments and results from teacher’ evaluations.